Spectral Analysis of 4f-4f Transitions for the Interaction of Nd(III) with L-Histidine in the Presence and Absence of Zn(II) in Different Organic Solvents - Singh, N. Mohondas; Gogoi, Jogat; Lallianmawii, . (Challenges and Advances in Chemical Science Vol. 7, 2021)
Various parameters such as percent covalency (\(δ\)), the Slater-Condon (Fk), the Nephelauxetic ratio (\(β\)), bonding parameters (b1/2), Lande orbit-spin coupling (\(ξ\)4f), have been estimated for the Nd(III)-L-histidine complex using their absorption spectra as a probe. Divergent solvents namely acetonitrile, DMF, methanol, dioxane were used and investigated the effect of Zn(II) ion in the complexation. The variations based on these parameter values disclose and reveal the bond formation between L-histidine and Nd(III). From the bond formation, we confirm that the DMF solvent promotes the 4f-4f dipole electric intensities compared to the other solvents investigated. The Judd-Ofelt parameter, given by T\(Λ\) (\(Λ\) = 2,4,6), gives the electronic dipole transition and theoretical calculations have been carried out to obtain the oscillator strength for Nd(III) complexation with L-histidine in the presence and the absence of Zn(II) in various aquated solvents which are organic, i.e., acetonitrile, 1,4-dioxane, N,N-dimethylformamide(DMF), and methanol.